Emergency Endoscopy after Gastrointestinal Haemorrhage in 50 Patients with Portal Hypertension. Issue 5936 (12th October 1974) - Waldram, R.; Davis, M.; Nunnerley, Heather; Williams, Roger
Abstract : Endoscopy was carried out in 50 patients with oesophageal varices within 24 hours of a major haematemesis or melaena. Sources of bleeding were identified in 42 of the cases and in only 19 patients was bleeding due to oesophageal varices. Bleeding from gastric varices was present in 11 patients, and a variety of acute and chronic lesions made up the remainder. In contrast with previous series haemorrhage from erosive gastric lesions was seen in only five patients and was no more common in 23 patients with alcoholic cirrhosis than in the group as a whole.